2017
DOI: 10.4183/aeb.2017.282
|View full text |Cite
|
Sign up to set email alerts
|

Low 06-Methylguanine-DNA Methytransferase (MGMT) and Pan-Cytokeratin (PAN-CK) Expression via Immunohistochemistry in Pituitary Adenomas

Abstract: Introduction. Pituitary adenomas (PA) are the third most common intracranial tumors, with an incidence rate of 10-15%. More than half are invasive, infiltrating adjacent structures. The primary objective of this project was to determine whether MGMT expression is associated with the invasiveness of PA. Material and Method. All patients who underwent surgical decompression consecutively between 2007-2012 were included. All data were obtained from the case records. Formalin-fixed paraffin-embedded (FFPE) tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Therefore, positivity of p53 expression is associated with p53 mutations [9]. It was shown that non-invasive and invasive adenomas and pituitary carcinomas exerted expression of p53 in 0, 15.2, and 100 % of cases, respectively, which correlated with invasion in a recent study [7]. In addition, it was shown that non-functioning pituitary adenomas are non-reactive for p53, while functional pituitary adenomas express p53, and functioning adenomas have more aggressive features than nonfunctioning adenomas including immunoreactivity for p53, S100, prolactin and MGMT (methylguanine methyltransferase) [7].…”
Section: Are the Invasive Prolactinomas Aggressive Prolactinomas Malignant Prolactinomas And Pituitary Carcinomas Different Entities? Anamentioning
confidence: 92%
See 4 more Smart Citations
“…Therefore, positivity of p53 expression is associated with p53 mutations [9]. It was shown that non-invasive and invasive adenomas and pituitary carcinomas exerted expression of p53 in 0, 15.2, and 100 % of cases, respectively, which correlated with invasion in a recent study [7]. In addition, it was shown that non-functioning pituitary adenomas are non-reactive for p53, while functional pituitary adenomas express p53, and functioning adenomas have more aggressive features than nonfunctioning adenomas including immunoreactivity for p53, S100, prolactin and MGMT (methylguanine methyltransferase) [7].…”
Section: Are the Invasive Prolactinomas Aggressive Prolactinomas Malignant Prolactinomas And Pituitary Carcinomas Different Entities? Anamentioning
confidence: 92%
“…It is recommended the term "aggressive" should not be used synonymously with "invasive" as aggressivity encompasses a broader biologically ominious behavior including drug resistance and occasionally atypical histology besides invasiveness [5]. In general, invasiveness is mostly a radiological and aggressiveness a clinical definition [7]. Invasive prolactinomas are tumors with proven invasion into adjacent structures, including cavernous and sphenoid sinuses and bony structures, which can be defined radiologically with preoperative MR investigations, during operation, or with histopathological demonstration of tumor spread to the bone, dura, or nasal mucosa [7].…”
Section: Are the Invasive Prolactinomas Aggressive Prolactinomas Malignant Prolactinomas And Pituitary Carcinomas Different Entities? Anamentioning
confidence: 99%
See 3 more Smart Citations